Chapter Predicting universal phonological contrasts - Lahiri, Aditi (Phonology and Phonetics [PP], 2018)
Despite earlier work by Trubetzkoy, Jakobson and Greenberg, phonological typology is often underrepresented in typology textbooks. At the same time, most phonologists do not see a difference between phonological typology and cross-linguistic (formal) phonology. The purpose of this book is to bring together leading scholars to address the issue of phonological typology, both in terms of the unity and the diversity of phonological systems.